Anterior lens capsule strains during simulated accommodation in porcine eyes. (March 2018) - Pellegrino, Antonio; Burd, Harvey John; Pinilla Cortés, Laura; D'Antin, Justin Christopher; Petrinic, Nik; Barraquer, Rafael I.; Michael, Ralph
Abstract: Experimental protocols have been developed to measure the spatial variation of the mechanical strains induced in the lens capsule during ex vivo lens stretching. The paper describes the application of these protocols to porcine lenses. The deformations and mechanical strains developed in the anterior capsule during each experiment were determined using full field digital image correlation techniques, by means of a speckle pattern applied to the lens surface. Several speckling techniques and illumination methods were assessed before a suitable combination was found. Additional data on the cross section shape of the anterior lens surface were obtained by Scheimpflug photography, to provide a means of correcting for lens curvature effects in the determination of the strains developed in the plane of the capsule. The capsule strains in porcine lenses exhibit non-linear behaviour, and hysteresis during loading and unloading. Peripheral regions experience higher magnitude strains than regions near the lens pole. The paper demonstrates the successful application of a procedure to make direct measurements of capsule strains simultaneously with ex vivo radial lens stretching. This experimental technique is applicable to future investigations on the mechanical characteristics of human lenses. Highlights: A digital image correlation protocol for the measurement of strains during radial lens stretching tests has been developed. The observed strain fields in the anterior capsule of porcine lenses indicate a consistent pattern of axial symmetry. The strain magnitudes increase with distance from the lens pole. The strain data obtained using this technique could be used to check the veracity of computational models of accommodation.